(untitled) (Sinología hispánica. China Studies Review, 2025)
Media play a crucial role in constructing and projecting a country’s image. This study examines how China is portrayed in its efforts to combat climate change through reports on the “double carbon” initiative published in the Spanish edition of People’s Daily between March 2023 and April 2024. Utilizing corpus analysis and positive discourse analysis, we analyzed high-frequency keywords, keyword collocation networks, and concordance lines to interpret China’s image. The results indicate that People’s Daily constructs a multifaceted image of China as a responsible leader, technological innovator, sustainable, and internationally cooperative nation. These representations are based on key strategic motivations: the transmission of state will, the strengthening of discursive power, the promotion of traditional ecological heritage, and the commitment to the principle of common but differentiated responsibilities. This analysis deepens the understanding of the media-driven construction of Chinas image in environmental sustainability and climate policies, providing a reference for future studies on the “double carbon” discourse.